As emoções e sentimentos na literatura infantil: perspectiva vigotskiana - Marçal, Cleonice (2017)
The current essay deals with the historical-cultural theory of Lev Semenovich Vygotsky and his contribution to children's literature. It is justified both by the importance of Vygotsky's theory for the comprehension of the relations between emotions/feelings, children's literature and imagination/creativity, and by the need to produce pedagogical practices which make the kids develop the liking for literary reading and comprehension of emotions/feelings. The research, of a bibliographical and qualitative character, was based on Vygotsky's theory (1994; 1998; 1999; 2000; 2003; 2004a; 2004b). An analysis was made of how children's literature books, destined to the age group from 3 to 5 years old, approach emotions and feelings. The research started with the following problem: how do children's books accessible to children in the age range from 3 to 5 years of age in public schools, approach the emotions? The general objective was to understand the relationships between children's literature and the development of emotions / feelings and creativity/imagination according to Vygotsky's theory. In order to respond to the proposed problem, the children's literature books distributed to public schools of education in Brazil were analyzed through the National Library in School Program (PNBE / 2014). It was possible to conclude that most books of children's literature relate emotions and feelings as aesthetic expression and enjoyment of emotions. Only a minimal portion mentions moral and behavioral teachings. It was also verified the use of words in augmentative and diminutive forms that denote exaggeration and short texts with the presence of onomatopoeia. In the Vygotskian perspective, the work of art that has as its purpose the teaching of moral and behavioral order can cause adverse effects. The role of the work of art should be aesthetic enjoyment, and not serve as a pretext for teaching a certain content.